2018
DOI: 10.1002/cam4.1686
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of PD‐L1 expression in upper tract urothelial carcinoma varies according to platelet count

Abstract: Programmed cell death ligand‐1 (PD‐L1) is a ligand for programmed cell death‐1 (PD‐1) that negatively regulates T‐cell activation and plays a crucial role in suppressing anti‐tumor host immunity. Although PD‐L1 is a promising immunotherapy target in various cancers, including urothelial carcinoma (UC), the prognostic significance of PD‐L1 in UC is unclear. As platelets help protect tumor cells from immune elimination in the circulatory system, we hypothesized that tumor PD‐L1 and circulating platelets might sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 40 publications
(93 reference statements)
3
10
0
Order By: Relevance
“…In the study, PD-L1 was related to UTUC in T stage and tumor grade, and similar findings have been indicated in both UTUC and other types of tumors (23,24,32,33). Results indicated that PD-L1 could not promote the LVI of UTUC, while great heterogeneity existed in the five studies (13,(15)(16)(17)24). However, previous studies have demonstrated that high PD-L1 was related to presence of LVI of tumors (15,34,35).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In the study, PD-L1 was related to UTUC in T stage and tumor grade, and similar findings have been indicated in both UTUC and other types of tumors (23,24,32,33). Results indicated that PD-L1 could not promote the LVI of UTUC, while great heterogeneity existed in the five studies (13,(15)(16)(17)24). However, previous studies have demonstrated that high PD-L1 was related to presence of LVI of tumors (15,34,35).…”
Section: Discussionsupporting
confidence: 76%
“…We excluded records for the following reasons: article types or not relevant topics (n = 188), studies had few study samples (≤50) or follow-up duration less than 12 months (n = 4), not in English (n = 9), or insufficient survival data (n = 15). Finally, we included eight retrospective cohort studies (1,406 individuals) (13)(14)(15)(16)(17)(23)(24)(25) in the study (shown in Figure 1).…”
Section: Literature Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The responses strongly correlated with increased PD-1 expression by TILs and increased PD-L1 expression by tumor cells (Pardoll, 2012). Some published studies reported that PD-L1 expression was a negative predictor for prognosis (Zhang et al, 2016; Aghajani et al, 2018; Keller et al, 2018; Miyama et al, 2018), whereas some other studies manifested inconsistent results (Pardoll, 2012; Wang C. et al, 2017; Huang et al, 2018). Various analyses on diverse tumors have showed that the expression of PD-L1 can associate either with poor prognosis, better prognosis or have no connection with prognosis (Ohigashi et al, 2005; Ghebeh et al, 2006; Wu et al, 2006; Hamanishi et al, 2007; Hino et al, 2010; Pardoll, 2012; Iacovelli et al, 2016; Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The relation between unusual expression of PD-L1 and prognosis or response to the treatment has been observed in several cancers. For example, the relationship between PD-L1 expression and prognosis has been detected in different solid tumors, including urothelial carcinoma, non-small cell lung cancer (NSCLC), and ovarian cancer (9-11). Furthermore, several studies have investigated the relationship between the expression of PD-1/PD-L1 and survival in patients with CRC; some of them have shown that patients with overexpression of these molecules have better survival than others (12, 13), but other studies have illustrated opposite results or no relationship (14, 15).…”
Section: Introductionmentioning
confidence: 99%